Education on the role of digital media in personal data protection - Surbakti, Feliks Prasepta Sejahtera (Universitas Muhammadiyah Magelang, 2025)
The evolution of the digital era has brought fundamental changes to personal data protection governance, making this a crucial issue in modern society. This activity aimed to increase public awareness about digital security, highlight common data theft methods, and provide practical tips for protecting personal data. The methodology included a literature review of personal data protection regulations, including the Indonesian Personal Data Protection Law (UU No. 27 Tahun 2022), and an analysis of the role of digital media in raising awareness and providing privacy setting tools. The research findings were then disseminated through a national webinar. The results of this activity showed that public awareness of the role of digital media in personal data protection increased by 75%. This study concludes that the effective use of digital media is essential for educating the public and preventing data breaches, making it a vital tool in modern cybersecurity efforts.